Spotlight on ORNAC Members: An Interview With Patricia Pocock RN, Dipl.Nsg. ED., BSN. - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2018)
Patricia Pocock is a health care leader with experience in perioperative and surgical services system alignment and program planning. She is a graduate of the University of Windsor and a registered nurse. She has worked in many capacities at St. Joseph’s Health Care, London, ON, including leadership of the operating room, post-anaesthetic care unit, intensive care unit, respiratory therapy and lithotripsy program. Prior to retirement from St. Joseph’s, in 2005, she held the position of Director, perioperative services, urology clinic, and central processing. She was then involved in Perioperative Consulting for eleven years, including acting as Senior Consultant for the Surgical Efficiency Targets Program with the Ministry of Health, and then officially retired in June of 2017. Pat is a founding member, and past Co-Chair, of the Canadian Operating Room Leaders Network, Past- President of the Lung Association of Ontario, a founding member, Past-President and former Treasurer of the London and District Operating Room Nurses Association, and a past Board Member of the Operating Room Nurses Association of Canada. She was awarded the Excellence in Nursing, Leadership, Coaching and Mentorship Award from St. Joseph’s in 2003 and was a 1992 Sisters of St. Joseph Award for Excellence recipient. She is married to Rev. Bruce Pocock and has two sons and five very active grandchildren.